A Bradyzoite is a Bradyzoite is a Bradyzoite?. Issue 12 (December 2015) - Kim, Kami
Abstract : Bradyzoite forms of Toxoplasma gondii persist in tissue cysts for the lifetime of an infected host and can reactivate to cause clinical disease. It was thought that in vivo bradyzoites within tissue cysts are biologically inactive dormant forms that rarely replicate. Apparently, consensus was wrong.